Placing Cognitive Rigidity in Interpersonal Context in Psychosis: Relationship With Low Cognitive Reserve and High Self-Certainty - García-Mieres, Helena; Usall, Judith; Feixas, Guillem; Ochoa, Susana (Frontiers in Psychiatry, 2020)
Abstract Introduction: People with psychosis show impairments in cognitive flexibility, a phenomenon that is still poorly understood. In this study, we tested if there were differences in cognitive and metacognitive processes related to rigidity in patients suffering psychosis comparing individuals with dichotomous interpersonal thinking and those with flexible interpersonal thinking. Methods: Two groups with psychosis were evaluated, one with low levels of dichotomous interpersonal thinking (n = 42) and the other with high levels of dichotomous interpersonal thinking (n = 43), using a social-demographic questionnaire as well as a semi-structured interview to assess psychotic symptoms (PANSS), a self-report of cognitive insight (BCIS), neurocognitive tasks (WCST, WAIS) and the Repertory Grid Technique. Results: The group with high dichotomous interpersonal thinking had earlier age at onset of the psychotic disorder, higher self-certainty, impaired executive functioning, affected abstract thinking and lower premorbid IQ than the group with flexible thinking. According to the logistic regression model, self-certainty, followed by the premorbid IQ were the variables that better differentiated between those two groups. Conclusion. Cognitive rigidity may be a generalized cognitive bias that affects not only neurocognitive and metacognitive processes, but also the sense of self and significant others. Patients with high cognitive rigidity might benefit of interventions that target this cognitive bias on an integrative way and adapted to their general level of intelligence.